VD_FINDINFO LAVAM 18/12 - 8/2013 vom 20. August 2013 - VD Tribunal cantonal (2013)
RÉDUCTION DES PRIMESAM, CONJOINT, INDEMNITÉ DE CHÔMAGE, DÉCISION | 65 LAMal, 11 LVLAMal, 12 LVLAMal, 18 al. 2 LVLAMal, 9 LVLAMal, 26 RLVLAMal